2018
DOI: 10.3390/su10051685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sustainable Energy Security and an Empirical Analysis of China

Abstract: Abstract:Energy security and sustainability are crucial factors for the development of China. The creation of an evaluation theoretical system of the energy has theoretical and practical significance that is important for ensuring the safe and sustainable development of energy security that matches the national development phase and reflects the sustainable development of national energy. Sustainable energy security must not only take into account the security of energy supply-demand in the long-term and short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 48 publications
1
54
0
1
Order By: Relevance
“…The energy and climate sustainability of countries and/or groups of countries constitutes a vast area of scientific research. Studies that look at the concept of sustainable development can be found in the available literature [23,[40][41][42][43][44][45][46][47][48][49][50].…”
Section: Research About Sustainable Energy and Climate Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy and climate sustainability of countries and/or groups of countries constitutes a vast area of scientific research. Studies that look at the concept of sustainable development can be found in the available literature [23,[40][41][42][43][44][45][46][47][48][49][50].…”
Section: Research About Sustainable Energy and Climate Developmentmentioning
confidence: 99%
“…Research on sustainable energy development and its level has concerned various countries [40][41][42][43][44][45][46][47] or groups of countries [23,[48][49][50]. However, the available literature lacks studies devoted to the assessment of the level of sustainable energy development in the EU-27 over the past 10 years.…”
Section: Research About Sustainable Energy and Climate Developmentmentioning
confidence: 99%
“…"Diversification of sources for electricity generation" is one of the most significant indicators in terms of criteria weights. In recent studies, the importance of diversification of energy supply has been emphasized with other factors, such as political stability, energy resource availability, energy dependence, and reserve-to-production ratio [8,70,71]. Using the GRA method to create an additional energy security dimension by including such factors may provide a more comprehensive approach to rank countries in future works.…”
Section: Resultsmentioning
confidence: 99%
“…However, traditionally energy security has been measured mostly at country or regional level (Almeida Prado et al, 2016;Fang, Shi, & Yu, 2018;Greene, 2010;Hu & Ge, 2014;Jääskeläinen, ISSN 2337-7062 © 2019 This is an open access article under the CC-BY-NC-ND license (http://creativecommons.org/licenses/by-nc-sa/4.0/). -lihat halaman depan © 2019 *Email: yudha.prambudia@widyatama.ac.id.ac.id Diterima 11 Juni 2019, disetujui 27 Juli 2019 Höysniemi, Syri, & Tynkkynen, 2018;Kanchana & Unesaki, 2015;Kharlamova, Stavytskyy, & Chernyak, 2018;Kumar, 2016;Lisin, Strielkowski, Chernova, & Fomina, 2018;Löschel, Moslener, & Rübbelke, 2010;Martchamadol & Kumar, 2012;Narula & Reddy, 2016;Radovanović, Filipović, & Pavlović, 2017;Von Hippel, Suzuki, Williams, Savage, & Hayes, 2011;Watson & Scott, 2009;Yao & Chang, 2014).…”
Section: Introductionmentioning
confidence: 99%